Argumentation, Anger, and Action: Citizenship Education In and Out of the Classroom - Bendixen, Lisa (In Factis Pax: Journal of Peace Education and Social Justice, 2010)
This special issue brings together four articles that examine various frameworks and research on knowledge, skills, and dispositions associated with democratic citizenship education. The perspectives represented include developmental psychology, educational psychology, educational philosophy, psychoanalysis, and curriculum and instruction. Overall, the message from these viewpoints comes together with remarkable clarity in terms of generating ideas and evidence for the improvement of citizenship education. My goals for the current discussion include a description of four themes gleaned from the articles’ commonalities and differences, thoughts regarding educational implications, and suggestions for future considerations and research).